2013
DOI: 10.1159/000349884
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Cell Carcinoma of the Ureteric Stump: A Systematic Review of the Literature

Abstract: Objective: To present a review of the literature using evidence-based criteria for diagnosis and treatment of malignant growths in the ureteric remnant following nephrectomy for non-malignant disease. Methods: A database search using the key search words was performed, producing a total of 16 articles published between 1952 and 2009. The Oxford Centre for Evidence-Based Medicine classification was used. Statistical significance was tested by Pearson correlation. Demographic data, reason for nephrectomy, sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Nevertheless, the remaining ureteral stump in partial ureterectomy can cause complications. The most common complications related to the ureteral stump are UTI, empyema with or without calculi, pain, hematuria, malignant transformation, and fungal peritonitis 6,7,63–68 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the remaining ureteral stump in partial ureterectomy can cause complications. The most common complications related to the ureteral stump are UTI, empyema with or without calculi, pain, hematuria, malignant transformation, and fungal peritonitis 6,7,63–68 …”
Section: Discussionmentioning
confidence: 99%
“…The most common complications related to the ureteral stump are UTI, empyema with or without calculi, pain, hematuria, malignant transformation, and fungal peritonitis. 6,7,[63][64][65][66][67][68] Different approaches for the management of symptomatic ureteral stumps have been introduced. While open and laparoscopic surgeries for stump removal are widely practiced, 6,64,65,69 some authors have also reported less invasive approaches.…”
Section: Ureteral Stump Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple techniques are described for the minimally invasive excision of the distal ureter and a bladder cuff (2-6). Unfortunately, many techniques ligate the ureter extravesically and several centimeters of intravesical ureter may remain, which may develop into malignancy (18). A study by Matin and Gill (19) demonstrated the higher positive surgical margin rate, reduced bladder cancer recurrence free survival, and reduced overall survival when using extravesical laparoscopic stapling.…”
mentioning
confidence: 99%